A quantitative spatiotemporal atlas of gene expression in the Drosophila blastoderm. - Fowlkes, C.C.; Luengo Hendriks, C.L.; Keränen, S.V.E.; Weber, G.H.; Rübel, O.; Huang, M.Y.; Chatoor, S.; DePace, A.H.; Simirenko, L.; Henriquez, C.; Beaton, A.; Weiszmann, R.; et al. (Cell, 2008)
To fully understand animal transcription networks, it is essential to accurately measure the spatial and temporal expression patterns of transcription factors and their targets. We describe a registration technique that takes image-based data from hundreds of Drosophila blastoderm embryos, each costained for a reference gene and one of a set of genes of interest, and builds a model VirtualEmbryo. This model captures in a common framework the average expression patterns for many genes in spite of significant variation in morphology and expression between individual embryos. We establish the method's accuracy by showing that relationships between a pair of genes' expression inferred from the model are nearly identical to those measured in embryos costained for the pair. We present a VirtualEmbryo containing data for 95 genes at six time cohorts. We show that known gene-regulatory interactions can be automatically recovered from this data set and predict hundreds of new interactions.